Hydrodynamics and flow field of a 6:1 prolate spheroid in maneuvering state: Numerical simulation and experimental investigation - Guo, Chun-yu; Gao, Ming-chen; Wang, Shi-min; Wang, Chao; Han, Yang (Physics of fluids (1994), 2025)
To address the critical issue of hydrodynamic and flow field dynamic response in predicting the maneuverability of underwater vehicles, a hydrodynamic analysis method for maneuvering motion is developed, utilizing numerical simulation and comparison with towed pool tests, focusing on a 6:1 prolate spheroid as the subject of investigation. The dynamic pressure response of a prolate spheroid subjected to pure sway, pure yaw, and coupled sway-yaw motions (including in-phase coupling, IPC, and quadrature-phase coupling, QPC) is systematically examined through experimental validation of an adapted novel horizontal motion mechanism, revealing the correlation between the peaks and troughs of pressure coefficients and the flow field structure. The results indicate that (i) hydrodynamic variations under pure sway, pure yaw, and IPC conditions exhibit a notable positive correlation, in which IPC amplifies the angle-of-attack effect via phase synchronization. (ii) The QPC condition demonstrates distinct nonlinear hydrodynamic properties resulting from the periodic disruption of the yaw-induced vortex structure by the sway motion: the pressure differential is positively correlated with yaw amplitude and negatively correlated with sway amplitude, while the peak-to-valley pressure difference increases sharply with a sudden frequency change (0.3 Hz). (iii) The flow separation method mainly influences the disparity in pressure response; the IPC condition is likely to generate significant transient shock loads, whereas the QPC condition emphasizes the nonlinear effects of motion coupling. The research findings establish a theoretical foundation for modeling fluid–solid interactions in underwater vehicle maneuvers.